Co-producing a Community University Knowledge Strategy - Bell, Sarah; Lee, Richard; Fitzpatrick, Daniel; Mahtani, Sona (Frontiers in Sustainability, 2021)
This community case study describes the process of developing a strategy for community-university engagement, as an example of co-production, and presents the strategy and early outcomes of the work. Based in London, the strategy and the process of co-production are of international relevance in supporting more productive relationships between universities and their cities, as a foundation for repurposing universities for sustainable human progress. The case study is presented in the context of literature related to community engagement with universities and co-production, an area of growing concern as universities seek to strengthen relationships and contribution to sustainable human progress in their home cities. London is one of the world’s great university cities, with more than 40 higher education institutions contributing ground-breaking research and educating students from across the globe. London is also home to vibrant local communities, with a strong tradition of grassroots action, community organization and citizen participation. Community groups and universities have a strong history of working together, often without formal recognition or resources. The Community University Knowledge Strategy for London, known as Collaborate!, was a collaboration between universities and grassroots community groups in London, co-convened by Just Space and University College London (UCL). A series of workshops, guided by two steering committees of community and university members, explored principles for working together, cultural and institutional barriers, decolonization, industrial strategies, community spaces and case studies of good practice. The final conference outlined the basis for a London-wide strategy to enable better engagement between universities and grassroots community groups. The strategy addresses core principles, curriculum, evaluation and evidence, resources, relationship building, governance and structures to support collaboration. Co-production ensured high levels of trust between participants and commitment to the outcomes. Implementation of the strategy actions requires ongoing resources to support intermediary structures to overcome misalignment between universities as large, hierarchical institutions and community groups as dynamic, informal, social organisations.